MEANS OF ENSURING CONTINUITY IN FORMING STUDENTS' INTEREST IN SPORTS CLUBS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article is dedicated to the effective use of integrated educational technologies in developing students' interests in sports clubs. The study analyzes the essence, main principles, and practical application possibilities of integrated educational technologies in sports sessions. In addition, the article examines modern pedagogical approaches as important tools for enhancing students’ activity, motivation, and individual abilities. The results indicate that integrated educational technologies serve as an effective mechanism for the sustainable development of students’ interests in sports clubs and for shaping their physical as well as moral and ethical qualities.